Metode Internalisasi Nilai-Nilai Moral Agama Islam Dalam Proses Pembelajaran Di Universitas KH.A.Wahab Hasbullah Tambakberas Jombang - Waslah - (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2017)
This study aims to describe the strategy of Internalization of Islamic moralvalues in the learning process at the University of KH. A. Wahab HasbullahTambakberas Jombang. Through the description of the strategy, it isexpected to find the right method to internalize Islamic moral values in thelearning process at Universitas KH.A. Wahab Hasbullah TambakberasJombang. This research is descriptive research using qualitative approach.Research subjects are lecturers who teach in Information ManagementStudies Program, Economics Study Program Faculty of EngineeringInformation and Management, at the University of KH. A. WahabHasbullah Tambakberas Jombang. Data were collected through interviews,observation, and documentation. Technique examination of data validityused is triangulation technique. The results showed that the strategy ofinternalization of Islamic moral values in learning include: modeling,analysis of actual problems that are developing in society, the planting ofcontextual educational values, and the strengthening of Islamic moralvalues that have been previously owned by students.